The Influence of Servant Leadership, Self-Efficacy, and Work Values on Teacher Engagement in Modern Education - Fitriyani Fitriyani; Didik Notosudjono; Widodo Sunaryo (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to analyze the influence of servant leadership, self-efficacy, and values on teacher engagement among public senior high school teachers with civil servant (ASN) status and private senior high school teachers with permanent foundation teacher (GTY) status in Bogor Regency. This research employed a quantitative approach using an ex-post facto and causal comparative design. The sample consisted of 255 teachers selected through multistage random sampling. Data were collected using questionnaires and analyzed using descriptive statistics, regression analysis, comparative analysis, and SITOREM analysis. The results showed that servant leadership, self-efficacy, and values had positive and significant effects on teacher engagement in both groups. Values emerged as the strongest predictor among ASN teachers, while self-efficacy was the dominant variable among GTY teachers. The findings also revealed differences in engagement characteristics between public and private school teachers, indicating that institutional context and employment status influence teachers’ psychological attachment and professional commitment. This study concludes that strengthening leadership practices, teachers’ self-efficacy, and organizational values is essential for improving teacher engagement and educational effectiveness.